Caring for your migrant patients and providing for their needs. (2nd July 2019) - Crawshaw, Alison; Hornigold, Rachael; Mandal, Sema; Campos-Matos, Ines
Abstract : Most migrants who come to the UK are young and healthy adults, but some have specific health needs that may be less familiar to health practitioners. This article describes migration patterns and highlights key points for migrant-sensitive care in general practice The UK has a long history of migration and in 2018 an estimated 14% of the population were born overseas. As international migration and displacement continue to rise, understanding how to care for migrant patients is of increasing importance for health professionals. This article describes migration trends in the UK and suggests considerations for care relating to key aspects of migrant health in general practice, including migrants' entitlements to the NHS, immunisation, infectious disease surveillance, testing and treatment, mental health, human trafficking and sociocultural considerations. It also highlights useful resources.